Are there Sex differences in Return to Play Rates in High Level Athletes Following Hip Arthroscopy?. Issue 7 (31st July 2020) - Dooley, Matthew; Burger, Joost; Kelly, Bryan; O'Sullivan, Eilish
Objectives: Return to sport is a common co ncern in those undergoing arthroscopic surgery for the treatment of femoroacetabular impingement. These are commonly young active individuals with high-level athletic aspirations. Setting expectations in terms of appropriate time frame and success rates are an integral piece of pre-operative education and planning. The goals of this study were to examine return to play (RTP) rates and time frames in professional and collegiate athletes following hip arthroscopy, evaluate sex differences in return to play (morphology and rates), and evaluate differences in return to play for the most common sports. Methods: A retrospective review of a continuous cohort of patients undergoing hip arthroscopy for the treatment of femoroacetabular impingement and labral injury was conducted between January 2014 and December 2018. Athletes whom were participating in collegiate or professional sports prior to surgery were included. Chart review was conducted to gather sport specific information, morphologic data, clearance dates, successful return, and subsequent surgery. Successful return to sport was determined by being able to return to participation following clearance in at least one season. Descriptive statistics were utilized to summarize the data set and chi-square and t-tests were utilized to examine differences between groups. Results: 265 patients undergoing 332 hip arthroscopies participating in collegiate or professional sports prior to surgery were identified (75.4% male and 24.6% female), with 237 collegiate athletes and 95 professional athletes. There was a significant difference in mean alpha angles between males and females, 70.2 ± 10.5 males and 60.7± 10.0 in females, (p<0.001), but no significant differences in coronal center edge angles or femoral version. 87% of the athletes participated in hockey, football, lacrosse, soccer, baseball, soccer, or basketball. Given that a significant portion of the athletes were in college, there was a portion that graduated and thus no longer participated in collegiate athletics (27 hips), and 3 athletes (all with bilateral hip arthroscopies) were unable to return to sport due to other conditions. 91.9% of athletes were able to return to sport. 19 athletes (22 hips) were unable to return to sport. The group that was unable to return was predominantly female (73%), and this difference was significant (p<0.001). There was a significant difference between the returning group and the group that failed to return to sport in alpha angle (RTP 68.6 ± 10.8 vs No RTP 60.7± 10.6), but there were no differences in coronal center edge angle or femoral version. The difference in alpha angle is due to the predominance of females (whom had significantly lower alphas) in the unable to return group. 10 athletes (11 hips, 3.3%) required subsequent surgery (revision arthroscopy, conversion to periacetabular osteotomy, or hip resurfacing). Times for return to play were available to 205 of the athletes, averaging 6.8 months± 2.8. There was no significant difference between the males and females for return to play. There was trend towards shorter length of return for hockey athletes. There was a significant difference in the return to sport rates between the sport groups, but there were some groups with smaller sample sizes that should be taken into account. The groups with more athletes unable to return were soccer and lacrosse; these sports also had a high number of female athletes. There were no hockey athletes that were unable to return, and only 1 football athlete was unable to return. Conclusions: Hip arthroscopy for the treatment of femoroacetabular impingement and labral injury allows patients to return to sport at a high level within an average of 6.8 months. However, female athletes are less likely to have a successful return and should potentially be counseled as such. This may also inform pre-operative rehabilitation programs and intra-operative planning for female athletes. Further research should examine causes for decreased rate of return for females, and potential ways to maximize recovery and return to sport following hip arthroscopy. Athletes' Ability to Return to Play by Sport Able Unable % RTP Football 52 1 98.20% Hockey 71 0 100.00% Soccer 21 5 80.80% Basketball 24 2 92.30% Baseball 32 2 94.10% Lacrosse 43 5 89.60%